National Standard Research in Universities - Herlina Herlina (CV. ADIBA AISHA AMIRA, 2022)
National Research Standards are the minimum criteria regarding the research system in universities that apply in all jurisdictions of the Unitary State of the Republic of Indonesia (NKRI) National Standards. This research also has several scopes and objectives that can be achieved by universities. In addition, a quality assurance system for higher education is needed, research-based learning and how to build a research culture in universities